2000
DOI: 10.1890/0012-9658(2000)081[0453:pcnicc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

PLANT CARBON–NUTRIENT INTERACTIONS CONTROL CO2EXCHANGE IN ALASKAN WET SEDGE TUNDRA ECOSYSTEMS

Abstract: We explored the long‐term (8‐yr) effects of separate field manipulations of temperature and nutrient availability on carbon balance in wet sedge tundra near the Arctic Long Term Ecological Research (LTER) site at Toolik Lake, Alaska. Our goals were (1) to assess the relative importance of chronic warming (with field greenhouses) and increased N and P availability (by fertilization) in controlling gross ecosystem photosynthesis, ecosystem respiration (plant plus heterotrophic respiration), and ultimately ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 29 publications
4
50
1
Order By: Relevance
“…Other studies also showed an increase or no change in NEP under experimental warming (Johnson et al 2000;Marchand et al 2004;Luo 2007) temperature is less critical than other plant and ecosystem processes, such as shifted plant and microbial species composition (Peñuelas et al 2004(Peñuelas et al , 2007Zhang et al 2005;Harte et al 2006), changes in phenology and extension of growing seasons (Nemanti et al 2003;Cleland et al 2007;Sherry et al 2007), and altered nitrogen uptake and use efficiency (Rustad et al 2001;Melillo et al 2002;An et al 2005), in regulating terrestrial feedback to climate change.…”
Section: Carbon Cycle Feedback To Climate Warmingmentioning
confidence: 98%
“…Other studies also showed an increase or no change in NEP under experimental warming (Johnson et al 2000;Marchand et al 2004;Luo 2007) temperature is less critical than other plant and ecosystem processes, such as shifted plant and microbial species composition (Peñuelas et al 2004(Peñuelas et al , 2007Zhang et al 2005;Harte et al 2006), changes in phenology and extension of growing seasons (Nemanti et al 2003;Cleland et al 2007;Sherry et al 2007), and altered nitrogen uptake and use efficiency (Rustad et al 2001;Melillo et al 2002;An et al 2005), in regulating terrestrial feedback to climate change.…”
Section: Carbon Cycle Feedback To Climate Warmingmentioning
confidence: 98%
“…), partly because of the poor understanding of the role of nutrients in regulating ecosystem C dynamics in permafrost zones under warming scenarios (Johnson et al. , Keuper et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations report that thermal profiles of permafrost and northern latitude temperature records have risen 2°–4°C across northern Alaska and Canada during the last few decades [ Lachenbruch and Marshall , 1986; Oechel et al , 1993; Osterkamp and Romanovsky , 1999]. This change in temperature will eventually affect the hydrology and thermal regime as well as feedback processes of Arctic tundra ecosystems which will ultimately influence the direction and magnitude of the carbon budget of the Arctic tundra region [ Tieszen et al , 1980; Kane et al , 1991; Chapin and Shaver , 1996; Johnson et al , 1996, 2000; Oechel et al , 2000b; Chapin et al , 2005].…”
Section: Introductionmentioning
confidence: 99%